Clinical Features and Gut Microbial Alterations in Anti-leucine-rich Glioma-Inactivated 1 Encephalitis—A Pilot Study - Ma, Xueying; Ma, Lili; Wang, Zhanhang; Liu, Yingying; Long, Ling; Ma, Xiaomeng; Chen, Hao; Chen, Zhaoyu; Lin, Xiuli; Si, Lei; Chen, Xiaohong (Frontiers in Neurology, 2020)
Anti-leucine-rich glioma-inactivated 1 (anti-LGI1) encephalitis is a rare autoimmune encephalitis (AE). We investigated the clinical features and gut microbial alterations of anti- LGI1 encephalitis. Fifteen patients newly diagnosed with anti-LGI1 encephalitis were recruited in the study prior to the administration of immunotherapy. The control group contains 25 well-matched healthy controls (HCs). All participants were Han Chinese from South China. Their clinical data and fecal samples were collected. The diversity and composition of gut microbiota were analyzed by 16S ribosomal RNA (16S rRNA) gene sequencing. The results showed that anti-LGI1 encephalitis was characterized by cognitive impairment, faciobrachial dystonic seizures, hyponatremia and psychiatric symptoms. Abnormal EEG and brain MRI were presented in 9 and 10 patients, respectively. Compared to HCs, the anti-LGI1 encephalitis patients exhibited a decreased microbial diversity and an altered overall composition of gut microbiome. At the phylum level, anti-LGI1 encephalitis patients exhibited a higher abundance of Proteobacteria and lower abundance of Firmicutes. The alterations in the phylum level were associated with autoimmune and inflammatory disorders. At the genus level, there was an increase in Sphingomonas, Anaerofustis, Succinvibrio, Clostridium and SMB53 (genera related to movement disorders, psychiatric diseases and with pro-inflammatory effects). However, the Faecalibacterium, Roseburia, Lachnospira, Ruminococcus and Blautia (genera with ability to produce short-chain fatty acids (SCFAs)) were obviously reduced in the patient group. Our results suggest that anti-LGI1 encephalitis is characterized by special clinical features and is accompanied by alterations in specific gut microbiota. For the limited sample size and non-applicability to other populations, further studies are warranted to explore the relationships between gut microbiota and anti-LGI1 encephalitis.